2021
DOI: 10.3389/fonc.2021.705384
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Inhibition Disrupts Carboplatin Resistance in Isogenic Models of Triple-Negative Breast Cancer

Abstract: Triple-Negative Breast Cancer (TNBC) is the most aggressive breast cancer subtype, characterized by limited treatment options and higher relapse rates than hormone-receptor-positive breast cancers. Chemotherapy remains the mainstay treatment for TNBC, and platinum salts have been explored as a therapeutic alternative in neo-adjuvant and metastatic settings. However, primary and acquired resistance to chemotherapy in general and platinum-based regimens specifically strongly hampers TNBC management. In this stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 87 publications
(92 reference statements)
0
15
0
Order By: Relevance
“…Both WNT5A and WNT5B were reported to confer basal-like breast CSC properties by activating canonical and non-canonical Wnt signaling ( Shi et al, 2014 ; Jiang et al, 2019 ). In agreement, enhanced levels of stabilized β-catenin in TNBC cellular models have shown to increase stemness markers such as pluripotency genes and the total population of ALDH + and CD24 low /CD44 high CSCs promoting resistance to carboplatin ( Abreu de Oliveira et al, 2021 ).…”
Section: Wnt Signaling and Breast Cscsmentioning
confidence: 77%
See 1 more Smart Citation
“…Both WNT5A and WNT5B were reported to confer basal-like breast CSC properties by activating canonical and non-canonical Wnt signaling ( Shi et al, 2014 ; Jiang et al, 2019 ). In agreement, enhanced levels of stabilized β-catenin in TNBC cellular models have shown to increase stemness markers such as pluripotency genes and the total population of ALDH + and CD24 low /CD44 high CSCs promoting resistance to carboplatin ( Abreu de Oliveira et al, 2021 ).…”
Section: Wnt Signaling and Breast Cscsmentioning
confidence: 77%
“…This molecule is currently in phase I/II clinical trials in several solid malignancies, including TNBC ( Ghosh et al, 2019 ; Novartis, 2021 ). Interestingly, inhibition of PORCN by LGK974 has been shown to disable breast cancer stem cell activity in TNBC and to significantly reverse the acquired carboplatin resistance in the Patient-Derived Xenograft models ( Abreu de Oliveira et al, 2021 ).…”
Section: Opportunities and Challenges In Wnt Cancer Treatmentmentioning
confidence: 99%
“…Xenograft tumor model studies from carboplatin-resistant breast cancer patients found that canonical Wnt/β-catenin signaling activation upregulated the expression of tumor stem cell markers and promoted tumor resistance to carboplatin. Inhibition of the Wnt/β-catenin signaling pathway restored the sensitivity of tumor tissue to carboplatin [ 95 ] and reversed the resistance to enzalutamide in prostate cancer [ 96 ]. Studies have shown that frameshift mutations in TCF7, a positive transcriptional regulator in the WNT/β-catenin signaling pathway, can induce abnormal WNT/β-catenin signaling, activate glycogen synthase kinase-3 (GSK3), and induce resistance to gedatolisib in colon cancer cells [ 97 ].…”
Section: The Signaling Pathways In Tumor Drug Resistancementioning
confidence: 99%
“…Although the function of NOTUM gene is not fully elucidated yet, it has been reported that it is a negative regulator of Wnt signaling [ 25 ]. Since the deregulation of Wnt pathway plays an important role not only in the development of many different tumors, but also to the resistance of cancer cells to anticancer drugs [ 26 28 ], the upregulation of NOTUM by TTFields might have a therapeutic effect against resistant tumors.…”
Section: Discussionmentioning
confidence: 99%